Book Review: Cultural Resiliency and the Rise of Indigenous Media - Moscato, Derek (Media and Communication, 2016)
Valerie Alia’s book, The New Media Nation: Indigenous Peoples and Global Communication (New York: Berghahn Books, 2012, 270 pp.), points the way to major communication breakthroughs for traditional communities around the world, in turn fostering a more democratic media discourse. From Canada to Japan, and Australia to Mexico, this ambitious and wide-reaching work examines a broad international movement that at once protects ancient languages and customs but also communicates to audiences across countries, oceans, and political boundaries. The publication is divided roughly into five sections: The emergence of a global vision for Indigenous communities scattered around the world; government policy obstacles and opportunities; lessons from Canada, where Indigenous media efforts have been particularly dynamic; the global surge in television, radio and other technological media advances; and finally the longterm prospects and aspirations for Indigenous media. By laying out such a comprehensive groundwork for the rise of global Indigenous media over a variety of formats, particularly over the past century, Alia shows how recent social media breakthroughs such as the highly successful #IdleNoMore movement - a sustained online protest by Canada's First Nations peoples - have been in fact inevitable. The world’s Indigenous communities have leveraged media technologies to overcome geographic isolation, to foster new linkages with Indigenous populations globally, and ultimately to mitigate structural power imbalances exacerbated by non-Indigenous media and other institutions. (author's abstract)